Controlled Synthesis of N-Doped Hierarchical Porous Carbon Spheres Through Polydopamine for CO2 Adsorption and High-Performance Supercapacitors - Xiaoqi Jin; Jinlong Ge; Zhong Wu; Linlin Zhu; Mingwen Xiong; Jiahui Qi; Chengxiu Ruan (Molecules)
Hierarchical porous N-doped carbon spheres featuring a combination of micropores, mesopores and macropores as well as tuneable properties were synthesised using dopamine as a carbon precursor and triblock copolymers (F127, P123 and F127/P123 composites) as templates via direct polymerisation-induced self-assembly. The structures and textures of these materials were characterised using X-ray diffraction, scanning electron microscopy, transmission electron microscopy, N2 adsorption–desorption isotherm analysis, Fourier-transform infrared spectroscopy, Raman spectroscopy and X-ray photoelectron spectroscopy. The sample synthesised at an F127:P123 molar ratio of 1:3 (NCS-FP3) exhibited the highest surface area (463 m2/g) and pore volume (0.27 cm3/g). The hydrophobic/hydrophilic molar ratios of the templates were adjusted to control the morphology of the corresponding micelles and hence the porous structures and morphologies of the carbon spheres, which exhibited high CO2 capture capacities (2.90–3.46 mmol/g at 273 K and 760 mmHg) because of their developed microporous structures and N doping. Additionally, NCS-FP3 exhibited an outstanding electrochemical performance, achieving a high specific capacitance (328.3 F/g at a current density of 0.5 A/g) and outstanding cycling stability (99.2% capacitance retention after 10,000 cycles). These high CO2 capture and electrochemical performances were ascribed to the beneficial effects of pore structures and surface chemistry features.